Negative plate, preparation method thereof and battery
By adopting a double-layer coating structure on the negative electrode of the battery and using primary and secondary particle graphite materials, the problems of low capacity retention rate and slow charging speed during the fast charging process are solved, and the fast charging performance, capacity increase and stability and safety of the battery are improved.
Patent Information
- Application Number
- CN202411770907.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-03
AI Technical Summary
During the fast charging process, existing battery negative electrode chips have problems such as low capacity retention rate, slow charging speed, and low cycle life and safety.
The negative electrode sheet design adopts a double-layer coating structure, wherein the first negative electrode coating has a smaller magnification as the inner layer and the second negative electrode coating has a larger magnification as the outer layer. The first negative electrode active material includes primary particle graphite and the second negative electrode active material includes secondary particle graphite. The fast charging performance and capacity of the battery are improved by this structural design.
It achieves improved fast charging performance and capacity of the battery, while improving the stability and safety of the battery and extending the cycle life.
Smart Images

Figure CN119560501A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and more specifically, to a negative electrode sheet and a preparation method thereof, and a battery. Background Art
[0002] In the related art, the negative electrode sheet of the battery usually includes a current collector and a single-layer single-rate material layer arranged on the surface of the current collector. When a high-rate material is used to make a single-layer material layer on the surface of the current collector, the heat and stress inside the negative electrode sheet are small, and side reactions are very likely to occur in the battery, causing the internal structure of the material to be destroyed, thereby reducing the cycle life and safety of the battery. When a low-rate layer material is used to make a single-layer material layer on the surface of the current collector, the migration rate of lithium ions in the negative electrode sheet is slow, resulting in a slow charging speed, which cannot meet the fast charging requirements of today's batteries. Summary of the invention
[0003] The purpose of the embodiments of the present application is to provide a negative electrode sheet and a preparation method thereof, and a battery, which can meet the requirements of large battery capacity and fast charging performance, and can also improve the stability and safety of the battery.
[0004] In a first aspect, an embodiment of the present application provides a negative electrode sheet, comprising:
[0005] current collector;
[0006] A first negative electrode coating is disposed on the surface of the current collector, wherein the first negative electrode coating comprises a first negative electrode active material;
[0007] A second negative electrode coating is disposed on a side of the first negative electrode coating away from the current collector, and the second negative electrode coating comprises a second negative electrode active material;
[0008] The first negative electrode active material has a first magnification, the second negative electrode active material has a second magnification, and the first magnification is smaller than the second magnification.
[0009] In one embodiment, at the same rate and at a capacity retention rate not lower than a set capacity retention rate, the number of cycles X that the first negative electrode active material can maintain is less than the number of cycles Y that the second negative electrode active material can maintain.
[0010] In one embodiment, YX≥100.
[0011] In one embodiment, the first negative electrode active material maintains a capacity retention rate of not less than 80% at a first rate for a cycle number between 300 and 400, the second negative electrode active material maintains a capacity retention rate of not less than 80% at the first rate for a cycle number between 500 and 600, and the second negative electrode active material maintains a capacity retention rate of not less than 80% at the second rate for a cycle number between 300 and 400.
[0012] In one embodiment, the first magnification is 3C-5C, and the second magnification is 6C-10C.
[0013] In one embodiment, the mass of the first negative electrode coating accounts for w1% of the sum of the masses of the first negative electrode coating and the second negative electrode coating, and the mass of the second negative electrode coating accounts for w2% of the sum of the masses of the first negative electrode coating and the second negative electrode coating, wherein w1%:w2%=(60%-80%):(20%-40%).
[0014] In one embodiment, the first negative electrode active material includes primary graphite particles, and / or the second negative electrode active material includes secondary graphite particles.
[0015] In one embodiment, the first negative electrode active material includes first graphite particles, and the particle size of the first graphite particles is 11.3 μm to 11.7 μm;
[0016] And / or, the second negative electrode active material includes second graphite particles, and the particle size of the second graphite particles is 6.5 μm to 7.5 μm.
[0017] In one embodiment, the orientation degree of the first negative electrode active material is 10.4 to 11.4;
[0018] And / or, the orientation degree of the second negative electrode active material is 8.4 to 8.7.
[0019] In a second aspect, an embodiment of the present application provides a method for preparing a negative electrode sheet, comprising the following steps:
[0020] S10, providing a fluid collector;
[0021] S20, selecting a material with a first magnification as a first negative electrode active material, and selecting a material with a second magnification as a second negative electrode active material, wherein the first magnification is smaller than the second magnification;
[0022] S30, using the first negative electrode active material to prepare a first negative electrode coating material, and using the second negative electrode active material to prepare a second negative electrode coating material;
[0023] S40, coating the first negative electrode coating material on the surface of the current collector to form a first negative electrode coating;
[0024] S50, coating the second negative electrode coating material on a side of the first negative electrode coating facing away from the current collector to form a second negative electrode coating.
[0025] In one embodiment, the step S20 includes:
[0026] S21, setting the same rate to measure the capacity retention rate and the number of cycles of the materials in turn, selecting a material that can maintain a capacity retention rate of not less than the set number of cycles X as the first negative electrode active material, and selecting a material that can maintain a capacity retention rate of not less than the set number of cycles Y as the second negative electrode active material, wherein X is less than Y.
[0027] In one embodiment, the step S20 further includes YX≥100.
[0028] In one embodiment, in step S20,
[0029] Selecting the first negative electrode active material including first graphite particles, wherein the particle size of the first graphite particles is 11.3 μm to 11.7 μm;
[0030] and / or, selecting the second negative electrode active material comprising second graphite particles, wherein the particle size of the second graphite particles is 6.5 μm to 7.5 μm;
[0031] and / or, selecting the first negative electrode active material having an orientation degree between 10.4 and 11.4;
[0032] And / or, the second negative electrode active material is selected with an orientation degree between 8.4 and 8.7.
[0033] In a third aspect, an embodiment of the present application provides a battery, comprising the above-mentioned negative electrode sheet or the negative electrode sheet prepared by the above-mentioned preparation method, and also comprising a positive electrode sheet and a separator, wherein the negative electrode sheet, the separator and the positive electrode sheet are stacked, and the separator is arranged between the positive electrode sheet and the negative electrode sheet.
[0034] The beneficial effect of the negative electrode sheet provided by the embodiment of the present application is that: compared with the related art, the negative electrode sheet of the present application includes a current collector, a first negative electrode coating arranged on the surface of the current collector, and a second negative electrode coating arranged on the side of the first negative electrode coating away from the current collector, wherein the first negative electrode active material has a first rate, the second negative electrode active material has a second rate, and the first rate is less than the second rate; the current collector surface of the negative electrode sheet of the present application includes a double-layer coating, and by setting the second negative electrode coating with a larger rate as the outer layer, a fast ion transmission channel is provided, so that the lithium ions outside the negative electrode sheet can quickly reach the inner layer through the outer layer for layer storage, and realize fast reception and conduction of current, thereby improving the fast charging performance of the battery; the first negative electrode coating with a smaller rate is set as the inner layer, so that the inner layer has a large and stable capacity to absorb the lithium ions transmitted by the outer layer, thereby increasing the capacity of the battery; and the first negative electrode coating is stable in nature, which can alleviate the structural changes inside the material of the second negative electrode coating, reduce the occurrence of side reactions, and thus ensure the overall stability and safety of the battery. The embodiment of the present application also provides a method for preparing a negative electrode sheet and a battery, which have the above-mentioned beneficial effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0036] Figure 1 A schematic diagram of the structure of a negative electrode sheet provided in one embodiment of the present application;
[0037] Figure 2 A scanning electron microscope characterization image of a negative electrode sheet provided in one embodiment of the present application;
[0038] Figure 3 A schematic diagram of a process for preparing a negative electrode sheet according to another embodiment of the present application;
[0039] Figure 4 for Figure 3 Schematic diagram of the structure of the negative electrode sheet preparation;
[0040] Figure 5 A schematic diagram of the structure of a battery provided in yet another embodiment of the present application;
[0041] Among them, the reference numerals in the figure are:
[0042] Battery 100; negative electrode sheet 10; housing 20; tab 30; current collector 11; first negative electrode coating 12; second negative electrode coating 13. DETAILED DESCRIPTION
[0043] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0044] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.
[0045] It should be understood that the terms "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0046] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0047] Please also read Figure 1 and Figure 2 Now, the negative electrode sheet 10 provided in one embodiment of the present application is described. Figure 1 As shown, the negative electrode sheet 10 includes a current collector 11, a first negative electrode coating 12 and a second negative electrode coating 13. Specifically, the first negative electrode coating 12 is disposed on the surface of the current collector 11, and the second negative electrode coating 13 is disposed on a side of the first negative electrode coating 12 away from the current collector 11.
[0048] The first negative electrode coating 12 includes a first negative electrode active material, and the second negative electrode coating 13 includes a second negative electrode active material; wherein the first negative electrode active material has a first rate, the second negative electrode active material has a second rate, and the first rate is smaller than the second rate.
[0049] The surface of the current collector 11 of the negative electrode sheet 10 provided in the embodiment of the present application includes a double-layer coating. By setting a second negative electrode coating 13 with a larger rate as the outer layer, a fast ion transmission channel is provided, so that the lithium ions outside the negative electrode sheet 10 can quickly reach the inner layer through the outer layer for layer storage, thereby realizing rapid reception and conduction of current, thereby improving the fast charging performance of the battery; a first negative electrode coating 12 with a smaller rate is set as the inner layer, so that the inner layer has a large and stable capacity to absorb the lithium ions transmitted by the outer layer, thereby increasing the capacity of the battery; and the first negative electrode coating 12 is stable in nature, which can alleviate the structural changes inside the material of the second negative electrode coating 13 and reduce the occurrence of side reactions, thereby ensuring the overall stability and safety of the battery.
[0050] Specifically, at the same rate and at a capacity retention rate not lower than a set rate, the number of cycles X of the first negative electrode active material is less than the number of cycles Y of the second negative electrode active material, that is, X < Y. At the same rate and at the same capacity retention rate, the number of cycles X of the first negative electrode active material is less than the number of cycles Y of the second negative electrode active material.
[0051] Optionally, the current collector 11 has a first surface and a second surface; the first negative electrode coating 12 is disposed on the first surface of the current collector 11, and the second negative electrode coating 13 is disposed on the side of the first negative electrode coating 12 away from the first surface of the current collector 11, or the first negative electrode coating 12 is disposed on the second surface of the current collector 11, and the second negative electrode coating 13 is disposed on the side of the first negative electrode coating 12 away from the second surface of the current collector 11, or the first negative electrode coating 12 is disposed on both surfaces of the current collector 11, and two second negative electrode coatings 13 are respectively disposed on the two surfaces of the first negative electrode coating 12 away from the current collector 11. In this embodiment, the first negative electrode coating 12 is disposed on both surfaces of the current collector 11, and the two second negative electrode coatings 13 are respectively disposed on the two surfaces of the first negative electrode coating 12 away from the current collector 11, so as to make full use of the current collector 11, increase the content of the first negative electrode active material and the second negative electrode active material, and improve the current transmission carrying capacity of the negative electrode sheet 10.
[0052] Generally speaking, when a certain rate is applied to a material, the capacity retention rate of the material continues to decrease as the number of cycles increases. It should be noted that C represents the charge and discharge capacity rate of the battery. 1C represents the current intensity when the battery is fully discharged in one hour. It should also be noted that the first negative electrode active material has a first rate, and the second negative electrode active material has a second rate. The present application selects the first negative electrode active material and the second negative electrode active material by applying the same rate conditions and maintaining the same capacity retention rate and comparing the number of cycles, and specifically, the first rate of the first negative electrode active material and the second rate of the second negative electrode active material still need to be determined by measurement.
[0053] In the present application, under the conditions of the same ambient temperature and the same magnitude of the rate applied, the number of cycles that the second negative electrode active material can achieve by maintaining a capacity retention rate is greater than the number of cycles that the first negative electrode active material can achieve by maintaining the same capacity retention rate. That is, at room temperature, the same rate is set to measure the capacity retention rate and the number of cycles of the materials in sequence. The capacity retention rate is set to 80%, and a material that maintains a cycle number X with a capacity retention rate of not less than 80% is selected as the first negative electrode active material, and a material that maintains a cycle number Y with a capacity retention rate of not less than 80% is selected as the second negative electrode active material, and X<Y. In other words, the cycle number X when the first negative electrode active material drops to 80% is less than the cycle number Y when the second negative electrode active material drops to 80%. In this embodiment, the first rate is set, that is, the first rate is applied to the materials in sequence to measure the capacity retention rate and the number of cycles.
[0054] Further, YX≥100. It can be understood that, at the same rate and with the same capacity retention rate, the greater the difference between the cycle number Y of the second negative electrode active material and the cycle number X of the first negative electrode active material, the greater the difference between the rate of the second negative electrode active material and the rate of the first negative electrode active material, so that the ions of the second negative electrode active material are more easily embedded and extracted, the greater the electronic conductivity and the ion diffusion rate, the faster the second negative electrode active material can absorb the charging current, so that the lithium ion concentration in the second negative electrode active material is higher than the lithium ion concentration in the first negative electrode active material; the lithium ion concentration in the second negative electrode active material is higher than the lithium ion concentration in the first negative electrode active material, so that lithium ions are more easily transferred from the second negative electrode active material to the first negative electrode active material; and the greater the difference between the rate of the second negative electrode active material and the rate of the first negative electrode active material, the greater the difference between the lithium ion concentration in the second negative electrode active material and the lithium ion concentration in the first negative electrode active material, further accelerating the migration of lithium ions from the second negative electrode coating 13 to the first negative electrode coating 12. Optionally, the difference between Y and X is between 100 and 200, or the difference between Y and X is between 200 and 300, or the difference between Y and X is between 300 and 400, etc.
[0055] In this embodiment, under the condition of applying the first rate, a material that can maintain a capacity retention rate of not less than 80% and a cycle number between 300 and 400 is selected as the first negative electrode active material, and a material that can maintain a capacity retention rate of not less than 80% and a cycle number between 500 and 600 is selected as the second negative electrode active material.
[0056] Specifically, the first rate refers to the rate at which the first negative electrode active material maintains a cycle number of 300 to 400 at a capacity retention rate of not less than 80% at room temperature. In other words, the first negative electrode active material having the first rate means that at room temperature, the first negative electrode active material is applied with the first rate, and the number of cycles when the capacity retention rate drops to 80% is between 300 and 400. Similarly, under the premise that the second rate is greater than the first rate and the ambient temperature is room temperature, the second rate refers to the rate at which the second negative electrode active material maintains a cycle number of 300 to 400 at a capacity retention rate of not less than 80%. In other words, the second negative electrode active material having the second rate means that at room temperature, the second negative electrode active material is applied with the second rate, and the number of cycles when the capacity retention rate drops to 80% is between 300 and 400.
[0057] For example, in this embodiment, the first rate is 3C, and the first negative electrode active material has a 3C rate; the second rate is 10C, and the second negative electrode active material has a 10C rate. At room temperature, the first negative electrode active material is subjected to a 3C rate and cycled. When the cycle reaches the 300th cycle, the capacity retention rate of the first negative electrode active material is greater than 80%, and when the cycle reaches the 400th cycle, the capacity retention rate of the first negative electrode active material is less than 80%; or, the number of cycles when the capacity retention rate of the first negative electrode active material drops to 80% is between 300 and 400. The second negative electrode active material is subjected to a 10C rate and cycled. When the cycle reaches the 300th cycle, the capacity retention rate of the second negative electrode active material is greater than 80%, and when the cycle reaches the 400th cycle, the capacity retention rate of the second negative electrode active material is less than 80%; or, the number of cycles when the capacity retention rate of the second negative electrode active material drops to 80% is between 300 and 400.
[0058] Continue to explain with this embodiment. At room temperature, a 3C rate is applied to the second negative electrode active material and cycled. When the cycle reaches the 400th cycle, the capacity retention rate of the second negative electrode active material is greater than 80%; or, the number of cycles when the capacity retention rate of the second negative electrode active material drops to 80% is greater than 400 (greater than the number of cycles of the first negative electrode active material under the same conditions). A 10C rate is applied to the first negative electrode active material and cycled. When the cycle reaches the 300th cycle, the capacity retention rate of the first negative electrode active material is less than 80%; or, the number of cycles when the capacity retention rate of the first negative electrode active material drops to 80% is less than 300 (less than the number of cycles of the second negative electrode active material under the same conditions).
[0059] Optionally, the first magnification is O1, O1=0.5k, where k is an integer greater than 0; the second magnification is O2, O2=0.5m, where m is an integer greater than k. In the process of selecting the first negative electrode active material and the second negative electrode active material, multiple magnifications from small to large are applied to the selected materials in sequence to screen out the first magnification material with a capacity retention rate of not less than 80% and the second magnification material with a capacity retention rate of not less than 80% and the cycle number of 500-600 cycles; in order to avoid repeated measurements, in the process of selecting materials, the first magnification O1 is directly applied to select the selected materials, so as to determine the first magnification material with a capacity retention rate of not less than 80% and the cycle number of 300-400 cycles between 300 and 400 between 300 and 400 between 300 and 400 between 300 and 6 ... During this selection process, the first rate O1 of the first negative electrode active material has also been determined; then the second rate O2 of the second negative electrode active material is measured to determine that the second negative electrode active material maintains a capacity retention rate of not less than 80% and maintains a second rate O2 of 300 to 400 cycles.
[0060] In order to improve the selection efficiency and simplify the selection steps, multiple magnifications are set as an arithmetic progression with a tolerance of 0.5C, so the first negative electrode active material with a first magnification O1 being a multiple of 0.5 and the second negative electrode active material with a second magnification O2 being a multiple of 0.5 greater than O1 are selected.
[0061] Alternatively, the first magnification is O1, O1=k, where k is an integer greater than 0; the second magnification is O2, O2=m, where m is an integer greater than k, which is specifically determined according to the tolerance between multiple magnifications during selection and measurement.
[0062] It is understandable that when the tolerance of multiple magnification settings is greater than 1C, the magnifications of multiple materials differ too much, resulting in too few selectable materials. When the tolerance of multiple magnification settings is less than 0.5C, the results of multiple magnification measurements on the same material are not much different, and the number of measurements is too many, resulting in too low material selection and measurement efficiency.
[0063] Optionally, in some other embodiments, O1=0.2k, O2=0.2m.
[0064] Optionally, the first rate is 3C to 5C, and the second rate is 6C to 10C. Specifically, the first rate is 3C, 3.5C, 4C, 4.5C or 5C, and the second rate is 6C, 6.5C, 7C, 7.5C, 8C, 8.5C, 9C, 9.5C or 10C. The first negative electrode active material with a first rate of 3C to 5C has a high capacity and stability. During the fast charging process, the first negative electrode active material located in the inner layer can store a large amount of lithium ions transferred from the outer layer, ensuring that the inner layer has sufficient capacity to accommodate the lithium ions quickly transferred from the outer layer during fast charging. The stability of the first negative electrode active material can improve the cycle life and safety of the battery. During the fast charging process, a large amount of heat and stress will be generated inside the battery. The stability of the first negative electrode active material can reduce the occurrence of side reactions in the negative electrode sheet 10 and the structural damage inside the material, thereby improving the cycle life and safety of the battery. The second negative electrode active material with a second rate of 6C to 10C has good electronic conductivity and ion diffusion rate. The second negative electrode active material of the outer layer can quickly receive and conduct the charging current. During the fast charging process, a large amount of current needs to quickly enter the negative electrode sheet 10. The second negative electrode active material can efficiently receive the current to provide current to the first negative electrode active material, reducing the accumulation and polarization of the current on the surface of the negative electrode sheet 10. The second negative electrode active material can quickly perform ion embedding and extraction reactions. During fast charging, lithium ions are quickly embedded in the negative electrode sheet 10 and quickly migrate in the negative electrode sheet 10, thereby speeding up the charging speed.
[0065] Furthermore, the difference between the second rate and the first rate is greater than 3C, that is, O2-O1>3. It can be understood that the greater the second rate of the second negative electrode active material, the easier it is for the ions of the second negative electrode active material to be embedded and extracted, the greater the electronic conductivity and the ion diffusion rate, thereby quickly absorbing the charging current, so that the lithium ion concentration in the second negative electrode active material is higher than the lithium ion concentration in the first negative electrode active material; the lithium ion concentration in the second negative electrode active material is higher than the lithium ion concentration in the first negative electrode active material, so that lithium ions are more easily transferred from the second negative electrode active material to the first negative electrode active material; and the greater the difference between the second rate and the first rate, the greater the difference between the lithium ion concentration in the second negative electrode active material and the lithium ion concentration in the first negative electrode active material, further accelerating the migration of lithium ions from the second negative electrode coating 13 to the first negative electrode coating 12.
[0066] In addition, the contact area between the negative electrode sheet 10 and the electrolyte will affect the infiltration of the electrolyte. When the electrolyte infiltration is low, the reaction sites of the positive and negative electrode active materials are reduced, which leads to an increase in the internal resistance of the battery, and then causes the battery temperature to rise. The difference between the lithium ion concentration in the second negative electrode active material and the lithium ion concentration in the first negative electrode active material can promote the infiltration of the electrolyte.
[0067] Optionally, the mass of the first negative electrode coating 12 accounts for w1% of the sum of the masses of the first negative electrode coating 12 and the second negative electrode coating 13, and the mass of the second negative electrode coating 13 accounts for w2% of the sum of the masses of the first negative electrode coating 12 and the second negative electrode coating 13, wherein w1%:w2%=(60%-80%):(20%-40%). Specifically, w1%:w2%=60%:40%, or, w1%:w2%=70%:30%, or, w1%:w2%=80%:20%, etc. It can be understood that the heavier the mass proportion of the first negative electrode coating 12, the greater the current capacity that can be stored by the first negative electrode coating 12 in the negative electrode sheet 10, and thus the greater the capacity of the battery; the heavier the mass proportion of the second negative electrode coating 13, the faster and more the second negative electrode coating 13 in the negative electrode sheet 10 can absorb lithium ions, thereby improving the fast charging capability of the battery.
[0068] In this embodiment, the first negative electrode active material includes first graphite particles, and the first graphite particles include primary graphite particles. The second negative electrode active material includes second graphite particles, and the second graphite particles include secondary graphite particles. The primary particles have a relatively complete crystal structure and fewer defects, so the transmission path of electrons inside the first negative electrode active material is relatively direct and smooth, and the conductivity is relatively good; the primary graphite particles in the first negative electrode active material are formed by granulation, graphitization, coating and carbonization of the raw materials of the first negative electrode active material, which can improve the conductivity of the first negative electrode coating 12. The secondary particles are agglomerated by the primary particles, and their morphology and structure enable them to form a higher stacking density when stacked, thereby improving the energy density of the negative electrode sheet 10. In addition, since the secondary particles are agglomerated by the primary particles, their surface is uneven, so the secondary particles have a larger surface area, which increases the contact area between the second negative electrode coating 13 and the electrolyte to a certain extent, promotes the transmission and reaction of ions, and thus improves the electrochemical performance of the negative electrode sheet 10.
[0069] Optionally, the first graphite particle also includes a first coating layer coated outside the primary particle, and the first coating layer is a solid carbon coating layer. The second graphite particle also includes a second coating layer coated outside the secondary particle, and the second coating layer is a liquid resin coating layer. The first graphite particle and the second graphite particle both include a first coating layer and a second coating layer at the nanoscale, respectively. The first coating layer and the second coating layer are both carbon coating layers with a crystalline structure, and the lattices of the two are wavy. Coating the surface of the primary particle with the first coating layer can improve defects such as cracks and holes on the surface of the primary particle, and improve the structural stability of the first graphite particle. Coating the surface of the secondary particle with the second coating layer can improve cracks and holes on the surface of the secondary particle. The first coating layer and the second coating layer are isotropic, which can provide more active centers and fast lithium ion transmission channels for the intercalation of lithium ions, reduce polarization, and promote the diffusion of lithium ions.
[0070] In this embodiment, the particle size of the first graphite particles is 11.3 microns (μm) to 11.7 microns, such as 11.3 μm, 11.4 μm, 11.5 μm, 11.6 μm or 11.7 μm, etc. The particle size of the second graphite particles is 6.5 μm to 7.5 μm, such as 6.5 μm, 6.6 μm, 6.7 μm, 6.8 μm, 6.9 μm, 7.0 μm, 7.1 μm, 7.2 μm, 7.3 μm, 7.4 μm or 7.5 μm, etc. It can be understood that the smaller the particle size, the better the rate performance of the material.
[0071] Further, the orientation degree of the first negative electrode active material is 10.4 to 11.4. Optionally, the orientation degree of the first negative electrode active material is 10.4, 10.5, 10.6, 10.8, 11.0, 11.2 or 11.4, etc. And / or, the orientation degree of the second negative electrode active material is 8.4 to 8.7. Optionally, the orientation degree of the second negative electrode active material is 8.4, 8.5, 8.6 or 8.7. The first negative electrode active material with an orientation degree of 10.4 to 11.4 and the second negative electrode active material with an orientation degree of 8.4 to 8.7 are arranged so that the crystal structures of the first negative electrode active material and the second negative electrode active material are easier for lithium ions to be inserted and removed during the charge and discharge process.
[0072] Orientation is a measure of the degree of orientation of a polymer, which mainly refers to the degree to which various structural units such as macromolecules or chain segments, including microcrystals, are regularly arranged along the fiber axis. In this application, the orientation of the material is determined by X-ray diffraction. X-ray diffraction is a method of analyzing the internal crystal structure of a material by measuring the diffraction pattern of the material under X-ray irradiation. In the determination of the orientation, the X-ray diffraction method infers the orientation of the material by analyzing the position and intensity of the diffraction peaks in the diffraction pattern.
[0073] Optionally, the first negative electrode coating 12 further includes a first conductive agent, a first suspending agent, a first binder and a first solvent. The mass ratio of the first negative electrode active material, the first conductive agent, the first suspending agent and the first binder is (95.8-97.6): (0.2-0.6): (1.0-2.0): (1.5-2.5). The second negative electrode coating 13 further includes a second conductive agent, a second suspending agent, a second binder and a second solvent. The mass ratio of the second negative electrode active material, the second conductive agent, the second suspending agent and the second binder is (95.8-97.6): (0.2-0.6): (1.0-2.0): (1.5-2.5).
[0074] Optionally, the first conductive agent and the second conductive agent are both conductive carbon black (Super P, SP), or other conductive agents. Conductive carbon black SP is a conductive carbon black similar to furnace black, which is agglomerated from primary particles with a diameter of about 40nm into primary aggregates of 150nm to 200nm, and then formed by subsequent processing such as agglomeration and artificial compression.
[0075] Optionally, the first suspending agent and the second suspending agent are both carboxymethyl cellulose lithium (CMC-Li). Optionally, the first solvent and the second solvent are both water (H2O).
[0076] Furthermore, the mass ratio of the first negative electrode active material in the first negative electrode coating 12 is less than the mass ratio of the second negative electrode active material in the second negative electrode coating 13, thereby increasing the mass ratio of the second negative electrode active material in the negative electrode sheet 10 and ensuring the fast charging capability of the negative electrode sheet 10. For example, the mass ratio of the first negative electrode active material in the first negative electrode coating 12 is 95.8%, and the mass ratio of the second negative electrode active material in the second negative electrode coating 13 is 97.6%. The mass ratio of the second binder in the second negative electrode coating 13 is less than the mass ratio of the first binder in the first negative electrode coating 12. By setting a larger content of the first binder in the first negative electrode coating 12, the adhesion between the first negative electrode coating 12 and the current collector 11 or the second negative electrode coating 13 is enhanced to prevent the negative electrode sheet 10 from falling off; the second binder is a low swelling binder, thereby effectively suppressing the thickness expansion during the battery cycle and improving the cycle life of the battery. For example, the first binder accounts for 2% in the first negative electrode coating 12, and the second binder accounts for 1% in the second negative electrode coating 13. In the present embodiment, the first binder and the second binder are both styrene butadiene rubber (SBR) type binders. Optionally, the model of the first binder is BTR-102 of Japan Ruiong, Liofol LA 9522 of BASF, etc. Optionally, the second binder includes one of carboxylated styrene butadiene rubber, modified styrene butadiene rubber or water-based styrene butadiene rubber. As long as the swelling rate of the second binder is less than 50%, and the amount of the second binder is less than the amount of the first binder. In the present application, a low swelling rate binder refers to a binder with a swelling rate of less than 50%, specifically, a swelling rate of 49%, 45%, 30%, 20% or 15%, etc.
[0077] In this embodiment, the mass ratio of the first negative electrode active material, the conductive carbon black, the first suspending agent and the first binder is 97.00%: 0.4%: 1.1%: 1.5%. The mass ratio of the second negative electrode active material, the conductive carbon black, the second suspending agent and the second binder is 97.5%: 0.4%: 1.1%: 1.0%.
[0078] See also Figure 3 and Figure 4 The present embodiment also provides a method for preparing a negative electrode sheet 10, which is used to prepare the negative electrode sheet 10 provided in the present embodiment. Figure 3 As shown, the method for preparing the negative electrode sheet 10 includes the following steps:
[0079] S10, providing a current collector 11;
[0080] S20, selecting a material with a first magnification as a first negative electrode active material, and selecting a material with a second magnification as a second negative electrode active material, wherein the first magnification is smaller than the second magnification;
[0081] S30, using the first negative electrode active material to prepare a first negative electrode coating material, and using the second negative electrode active material to prepare a second negative electrode coating material;
[0082] S40, coating a first negative electrode coating material on the surface of the current collector 11 to form a first negative electrode coating 12;
[0083] S50 , coating a second negative electrode coating material on a side of the first negative electrode coating 12 facing away from the current collector 11 to form a second negative electrode coating 13 .
[0084] The following describes the method for preparing the negative electrode sheet 10 by taking the preparation of the negative electrode sheet 10 provided in Example 1 as an example.
[0085] S10, providing a current collector 11, such as Figure 4 shown.
[0086] Next, step S20 is performed to select a first negative electrode active material and a second negative electrode active material.
[0087] Specifically, step S20 includes:
[0088] S21, setting the same rate to measure the capacity retention rate and the number of cycles of the materials in turn, and taking the material whose capacity retention rate is not less than the set capacity retention rate and the number of cycles is X as the first negative electrode active material; taking the material whose capacity retention rate is not less than the set capacity retention rate and the number of cycles is Y as the second negative electrode active material, where X is less than Y.
[0089] In this embodiment, the first rate is set to measure the capacity retention rate and the number of cycles of the materials in sequence, and the capacity retention rate is set to 80%. The material that can maintain the number of cycles X between 300 and 400 at a capacity retention rate of not less than 80% at the first rate is selected as the first negative electrode active material, and the material that can maintain the number of cycles between 500 and 600 at a capacity retention rate of not less than 80% at the first rate is selected as the second negative electrode active material.
[0090] The specific material selection and rate testing method are explained below.
[0091] The instrument used for material selection and rate testing is Xinwei equipment, and the selection and testing temperature is at room temperature. In this application, room temperature refers to 20° C. to 25° C. The materials to be selected include a variety of negative electrode active materials.
[0092] The material selection and rate test methods specifically include:
[0093] S201, leaving the material to be tested for 10 minutes;
[0094] S202, discharge at a constant current of 0.5C to 3.0V;
[0095] S203, leaving the material to be tested for 10 minutes;
[0096] S204, charging at constant current and constant voltage to 4.5V at multiple different currents, and cut-off at 0.02C;
[0097] Specifically, the multiple different currents include: 0.5C, 1.0C, 1.5C, 2.0C, 2.5C, 3.0C, 3.5C, 4.0C, 4.5C, 5.0C, 5.5C, 6.0C, 6.5C, 7.0C, 7.5C, and 8.0C.
[0098] That is, multiple arithmetic multipliers are set with a tolerance of 0.5C, and constant current and constant voltage charging is performed at multiple arithmetic multipliers from small to large. It can be understood that setting arithmetic multipliers with a tolerance of 0.5C can improve the efficiency of selection and simplify the steps of selection and measurement.
[0099] Optionally, the multiple different currents include: 1.0C, 2.0C, 3.0C, 4.0C, 5.0C, 6.0C, 7.0C, and 8.0C. If the tolerance of multiple current settings is greater than 1C, the magnifications of multiple materials differ too much, resulting in too few selectable materials. If the tolerance of multiple current settings is less than 0.5C, the results of applying multiple magnifications to the same material are not much different, and the number of measurements is too many, resulting in too low material selection efficiency.
[0100] Since the tolerance is set to an arithmetic progression of 0.5C under multiple rates / currents, the first rate O1 of the first negative electrode active material is selected as a multiple of 0.5. Specifically, the first rate O1 is set and applied to multiple materials, and the first negative electrode active material and the second negative electrode active material are selected. Among them, the first rate O1 of the first negative electrode active material has been determined, and the second rate O2 of the second negative electrode active material needs to be determined by subsequent measurements.
[0101] The second negative electrode active material is continuously measured at multiple rates / currents greater than the first rate O1 with a tolerance of 0.5 C. A second rate O2 of the second negative electrode active material is measured. Since the multiple rates / currents are set as an arithmetic progression with a tolerance of 0.5 C, the second rate O2 is a multiple of 0.5 greater than O1.
[0102] S205, leaving the material to be tested for 10 minutes;
[0103] S206, looping steps S21 to S25 for 3 times.
[0104] Repeat the above steps multiple times, record the rate applied to the material and the capacity retention rate and cycle number of the various materials to be tested. In this embodiment, the first rate O1 is set to 3C, and the first rate O1 is applied to various materials. The material that maintains the cycle number X between 300 and 400 with a capacity retention rate of not less than 80% is selected as the first negative electrode active material; the material that maintains the cycle number Y between 500 and 600 with a capacity retention rate of not less than 80% is selected as the second negative electrode active material, wherein Y>X and YX≥100. In other words, the first negative electrode active material maintains the cycle number between 300 and 400 with a capacity retention rate of not less than 80%, and the second negative electrode active material maintains the cycle number between 500 and 600 with a capacity retention rate of not less than 80%.
[0105] In the material selection process, the first rate O1 of the first negative electrode active material has been determined to be 3C, and the second rate O2 of the second negative electrode active material needs to be further measured to be determined. Specifically, in this embodiment, the first rate O1 is 3C, and the second rate O2 is 10C. It can be understood that the difference between Y and X is selected to be greater than or equal to 100, that is, YX≥100, so that the greater the difference in the rate between the second negative electrode active material and the first negative electrode active material, the greater the difference in the lithium ion concentration in the second negative electrode active material and the lithium ion concentration in the first negative electrode active material, further accelerating the migration of lithium ions from the second negative electrode coating 13 to the first negative electrode coating 12.
[0106] Further, a first negative electrode active material including first graphite particles is selected, and the particle size of the first graphite particles is 11.3 μm to 11.7 μm. And / or, a second negative electrode active material including second graphite particles is selected, and the particle size of the second graphite particles is 6.5 μm to 7.5 μm. And / or, a first negative electrode active material with an orientation degree between 10.4 and 11.4 is selected. And / or, a second negative electrode active material with an orientation degree between 8.4 and 8.7 is selected.
[0107] In this embodiment, the particle size of the first graphite particles is 11.3 microns (μm) to 11.7 microns, such as 11.3μm, 11.4μm, 11.5μm, 11.6μm or 11.7μm. The particle size of the second graphite particles is 6.5μm to 7.5μm, such as 6.5μm, 6.6μm, 6.7μm, 6.8μm, 6.9μm, 7.0μm, 7.1μm, 7.2μm, 7.3μm, 7.4μm or 7.5μm. It can be understood that the smaller the particle size, the better the rate performance of the material. Optionally, the orientation degree of the first negative electrode active material is 10.4, 10.5, 10.6, 10.8, 11.0, 11.2 or 11.4, etc. Optionally, the orientation degree of the second negative electrode active material is 8.4, 8.5, 8.6 or 8.7. The first negative electrode active material with an orientation degree of 10.4 to 11.4 and the second negative electrode active material with an orientation degree of 8.4 to 8.7 are arranged so that the crystal structures of the first negative electrode active material and the second negative electrode active material are easier for lithium ions to be inserted and removed during charge and discharge.
[0108] Then, step S30 is performed, wherein the first negative electrode active material is used to form a first negative electrode coating material, and the second negative electrode active material is used to form a second negative electrode coating material;
[0109] Specifically, the first negative electrode active material, the first conductive agent, and the first suspending agent are dry-mixed, and then the first binder and the first solvent are added respectively, mixed and stirred evenly to prepare the first negative electrode coating material slurry.
[0110] The first negative electrode active material, the first conductive agent, the first suspending agent and the first binder are prepared into a first negative electrode coating material slurry in a first solvent at a mass ratio of (95.8-97.6):(0.2-0.6):(1.0-2.0):(1.5-2.5). The first negative electrode coating material slurry has a viscosity of 3000mPa·s-5000mPa·s and a solid content of 40%-55%.
[0111] The first negative electrode active material includes first graphite particles, and the first graphite particles include primary graphite particles and a first coating layer coated outside the primary particles. The first coating layer is a solid carbon coating layer.
[0112] Specifically, the second negative electrode active material, the second conductive agent, and the second suspending agent are dry-mixed, and then the second binder and the second solvent are added respectively, mixed and stirred evenly to prepare the second negative electrode coating material slurry.
[0113] The second negative electrode active material, the second conductive agent, the second suspending agent and the second binder are prepared in a second solvent at a mass ratio of (95.8-97.6):(0.2-0.6):(1.0-2.0):(1.5-2.5) to form a second negative electrode coating material slurry. The viscosity of the second negative electrode coating material slurry is 2000mPa·s-4000mPa·s, and the solid content is 40%-45%.
[0114] The second negative electrode active material, the second conductive agent, the second suspending agent and the second binder are prepared in a second solvent at a mass ratio of (95.8-97.6):(0.2-0.6):(1.0-2.0):(1.5-2.5) to form a second negative electrode coating material.
[0115] The second negative electrode active material includes second graphite particles, the second graphite particles include secondary graphite particles and a second coating layer coated outside the secondary particles, and the second coating layer is a liquid resin coating layer.
[0116] The first conductive agent and the second conductive agent are both conductive carbon black. Optionally, the first binder is BTR-102 of Japan Zeon, Liofol LA 9522 of BASF, etc. Optionally, the second binder includes one of carboxylated styrene butadiene rubber, modified styrene butadiene rubber or water-based styrene butadiene rubber.
[0117] Optionally, the first suspending agent and the second suspending agent are both carboxymethyl cellulose lithium (Carboxymethyl Cellulose Lithium, CMC-Li). Optionally, the first solvent and the second solvent are both water (H2O).
[0118] Then, step S40 and step S50 are performed, the first negative electrode coating material is coated on the surface of the current collector 11 to form a first negative electrode coating 12; the second negative electrode coating material is coated on the side of the first negative electrode coating 12 away from the current collector 11 to form a second negative electrode coating 13. Figure 4 shown.
[0119] The mass ratio of the first negative electrode coating material and the second negative electrode coating material is calculated to be (60% to 80%): (20% to 40%). The first negative electrode coating material is coated on the surface of the current collector 11 by a double-layer coating machine, and the second negative electrode coating material is coated on the side of the first negative electrode coating 12 away from the current collector 11. After drying, the first negative electrode coating material forms the first negative electrode coating 12, and the second negative electrode coating material forms the second negative electrode coating 13, and a negative electrode sheet 10 of 200 μm to 300 μm is obtained. The mass of the first negative electrode coating 12 thus formed accounts for w1% of the sum of the mass of the first negative electrode coating 12 and the second negative electrode coating 13, and the mass of the second negative electrode coating 13 accounts for w2% of the sum of the mass of the first negative electrode coating 12 and the second negative electrode coating 13, w1%: w2% = (60% to 80%): (20% to 40%).
[0120] See also Figure 5 , the embodiment of the present application also provides a battery 100, including the negative electrode sheet 10 provided in the present application or the negative electrode sheet 10 prepared by the preparation method provided in the present application, and also including a positive electrode sheet and a separator. The negative electrode sheet 10, the separator and the positive electrode sheet are stacked, the separator is arranged between the positive electrode sheet and the negative electrode sheet 10, and the separator, the negative electrode sheet 10 and the positive electrode sheet form a core package. Optionally, the positive electrode sheet, the negative electrode sheet 10 and the separator each have multiple, and multiple positive electrode sheets, multiple separators and multiple negative electrode sheets 10 are stacked in sequence to form a laminated core package. Alternatively, multiple positive electrode sheets, multiple separators and multiple negative electrode sheets 10 are wound to form a roll core package. Optionally, the core package is square or cylindrical. The battery 100 also includes a shell 20 and a pole ear 30. The core package is arranged in the shell 20. The pole ear 30 includes a positive pole ear and a negative pole ear. The positive pole ear is connected to the positive electrode sheet, and the positive pole ear is connected to the positive electrode column on the shell 20. The negative electrode tab is connected to the negative electrode sheet 10 , and the negative electrode tab is connected to the negative electrode post on the housing 20 .
[0121] Example 1
[0122] The negative electrode sheet 10 of this embodiment includes a current collector 11 , a first negative electrode coating 12 disposed on the surface of the current collector 11 , and a second negative electrode coating 13 disposed on a side of the first negative electrode coating 12 away from the current collector 11 .
[0123] The first negative electrode coating 12 includes a first negative electrode active material, a first conductive agent, a first suspending agent, a first binder and a first solvent. The first negative electrode active material includes primary graphite particles coated with a solid phase carbon coating layer; the particle size of the first graphite particles is 11.3 μm to 11.7 μm; the orientation degree of the first negative electrode active material is 10.4 to 11.4; the first conductive agent is conductive carbon black SP; the first suspending agent is CMC-Li; the first binder is BTR-102 of Japan Zeon; and the first solvent is water. The mass ratio of the first negative electrode active material, the first conductive agent, the first suspending agent, and the first binder is 97.00%: 0.4%: 1.1%: 1.5%. The first magnification O1 of the first negative electrode active material is 3C.
[0124] The second negative electrode coating 13 includes a second negative electrode active material, a second conductive agent, a second suspending agent, a second binder and a second solvent. The second negative electrode active material includes secondary graphite particles coated with a liquid resin coating layer; the particle size of the second graphite particles is 6.5 μm to 7.5 μm; the orientation degree of the second negative electrode active material is 8.4 to 8.7; the second conductive agent is conductive carbon black SP; the second suspending agent is CMC-Li; the second binder is carboxylated styrene butadiene rubber; and the second solvent is water. The mass ratio of the second negative electrode active material, the second conductive agent, the second suspending agent, and the second binder is 97.50%: 0.4%: 1.1%: 1.0%. The second rate O2 of the second negative electrode active material is 10C.
[0125] The percentage w1% of the mass of the first negative electrode coating 12 to the sum of the masses of the first negative electrode coating 12 and the second negative electrode coating 13 is 70%, and the percentage w2% of the mass of the second negative electrode coating 13 to the sum of the masses of the first negative electrode coating 12 and the second negative electrode coating 13 is 30%, w1%:w2%=70%:30%.
[0126] The present application tests the negative electrode sheet 10 of Example 1, the negative electrode sheet of Comparative Example 1, and the negative electrode sheet of Comparative Example 2 and records the capacity retention rate and the number of cycles.
[0127] The negative electrode sheet to be tested is tested using Xinwei equipment; the test conditions are at room temperature of 20℃~25℃. The specific test method is:
[0128] P1, place the negative electrode to be tested for 10 minutes;
[0129] P2, discharge to 3.0V with 1C constant current;
[0130] P3, place the negative electrode to be tested for 10 minutes;
[0131] P4, charge the negative electrode sheet to be tested at 4.0C, 3.0C, and 2.0C constant current and constant voltage in sequence; charge to 4.20V at 4.0C, and cut off at 3.0C; charge to 4.33V at 3.0C constant current and constant voltage, and cut off at 2.0C; charge to 4.50V at 2.0C constant current and constant voltage, and cut off at 0.02C;
[0132] P5, place the negative electrode to be tested for 10 minutes;
[0133] P6, repeat steps P2 to P5, repeat 1000 times.
[0134] Please refer to Table 1, the first row is the number of cycles of battery charge and discharge, and the first column is the tested samples. The negative electrode sheet of Comparative Example 1 includes a current collector and a single-layer coating 1 disposed on the surface of the current collector, and the coating 1 is a coating made of the same material as the first negative electrode coating 12 of Example 1, and the ratio of the negative electrode active material in the coating 1 is 3C. The negative electrode sheet of Comparative Example 2 includes a current collector and a single-layer coating 2 disposed on the surface of the current collector, and the coating 2 is a coating made of the same material as the second negative electrode coating 13 of Example 1, and the ratio of the negative electrode active material in the coating 2 is 10C.
[0135] Table 1
[0136] 100 weeks 200 weeks 300 weeks 400 weeks 500 weeks 600 weeks 700 weeks 800 weeks Comparative Example 1 99.00% 96.4% 85.60% Comparative Example 2 99.56% 96.76% 95.34% 90.61% 80.35% Example 1 99.24% 98.47% 97.60% 95.6% 93.00% 92.1% 90.99% 87.62%
[0137] As can be seen from Table 1, the negative electrode sheet with only a single layer of coating 1 maintains a capacity retention rate of more than 80% for a maximum cycle number of 300 to 400 cycles; the negative electrode sheet with only a single layer of coating 2 maintains a capacity retention rate of more than 80% for a maximum cycle number of 500 to 600 cycles; and the negative electrode sheet 10 of Example 1 maintains a capacity retention rate of more than 80% for a cycle number of more than 700 cycles, and the maximum cycle number can even reach more than 800 cycles, and the rate performance is extremely excellent. The negative electrode sheet 10 of Example 1 has fast conduction and reaction capabilities, as well as high capacity and stability, and the battery has excellent fast charging performance.
[0138] Example 2
[0139] The negative electrode sheet 10 of this embodiment includes a current collector 11 , a first negative electrode coating 12 disposed on the surface of the current collector 11 , and a second negative electrode coating 13 disposed on a side of the first negative electrode coating 12 away from the current collector 11 .
[0140] The first negative electrode coating 12 includes a first negative electrode active material, a first conductive agent, a first suspending agent, a first binder and a first solvent. The first negative electrode active material includes primary graphite particles coated with a solid phase carbon coating layer; the particle size of the first graphite particles is 11.3 μm to 11.7 μm; the orientation degree of the first negative electrode active material is 10.4 to 11.4; the first conductive agent is conductive carbon black SP; the first suspending agent is CMC-Li; the first binder is BASF's Liofol LA 9522; the first solvent is water. The mass ratio of the first negative electrode active material, the first conductive agent, the first suspending agent, and the first binder is 97.00%: 0.2%: 1.3%: 1.5%. The first magnification O1 of the first negative electrode active material is 5C.
[0141] The second negative electrode coating 13 includes a second negative electrode active material, a second conductive agent, a second suspending agent, a second binder and a second solvent. The second negative electrode active material includes secondary graphite particles coated with a liquid resin coating layer; the particle size of the second graphite particles is 6.5 μm to 7.5 μm; the orientation degree of the second negative electrode active material is 8.4 to 8.7; the second conductive agent is conductive carbon black SP; the second suspending agent is CMC-Li; the second binder is water-based styrene-butadiene rubber; and the second solvent is water. The mass ratio of the second negative electrode active material, the second conductive agent, the second suspending agent, and the second binder is 97.50%: 0.2%: 1.3%: 1.0%. The second magnification O2 of the second negative electrode active material is 8C.
[0142] The percentage w1% of the mass of the first negative electrode coating 12 to the sum of the masses of the first negative electrode coating 12 and the second negative electrode coating 13 is 60%, and the percentage w2% of the mass of the second negative electrode coating 13 to the sum of the masses of the first negative electrode coating 12 and the second negative electrode coating 13 is 40%, w1%:w2%=60%:40%.
[0143] The present application tests the negative electrode sheet 10 of Example 2, the negative electrode sheet of Comparative Example 3, and the negative electrode sheet of Comparative Example 4 and records the capacity retention rate and the number of cycles.
[0144] The negative electrode sheet to be tested is tested using Xinwei equipment; the test conditions are at room temperature of 20℃~25℃. The specific test method is:
[0145] P1, place the negative electrode to be tested for 10 minutes;
[0146] P2, discharge to 3.0V with 1C constant current;
[0147] P3, place the negative electrode to be tested for 10 minutes;
[0148] P4, charge the negative electrode sheet to be tested at 4.0C, 3.0C, and 2.0C constant current and constant voltage in sequence; charge to 4.20V at 4.0C, and cut off at 3.0C; charge to 4.33V at 3.0C constant current and constant voltage, and cut off at 2.0C; charge to 4.50V at 2.0C constant current and constant voltage, and cut off at 0.02C;
[0149] P5, place the negative electrode to be tested for 10 minutes;
[0150] P6, repeat steps P2 to P5, repeat 1000 times.
[0151] Please refer to Table 2, the first row is the number of cycles of battery charge and discharge, and the first column is the tested samples. The negative electrode sheet of Comparative Example 3 includes a current collector and a single-layer coating 3 disposed on the surface of the current collector, and the coating 3 is a coating made of the same material as the first negative electrode coating 12 of Example 2, and the ratio of the negative electrode active material in the coating 3 is 5C. The negative electrode sheet of Comparative Example 4 includes a current collector and a single-layer coating 4 disposed on the surface of the current collector, and the coating 4 is a coating made of the same material as the second negative electrode coating 13 of Example 2, and the ratio of the negative electrode active material in the coating 4 is 8C.
[0152] Table 2
[0153] 100 weeks 200 weeks 300 weeks 400 weeks 500 weeks 600 weeks 700 weeks 800 weeks Comparative Example 3 99.00% 96.1% 85.08% Comparative Example 4 99.23% 97.1% 96.61% 91.31% 85.33% Example 2 99.54% 98.62% 97.32% 95.23% 93.70% 92.8% 92.01% 85.41%
[0154] As can be seen from Table 1, the negative electrode sheet with only a single layer of coating 3 maintains a capacity retention rate of more than 80% for a maximum cycle number of 300 to 400 cycles; the negative electrode sheet with only a single layer of coating 4 maintains a capacity retention rate of more than 80% for a maximum cycle number of 500 to 600 cycles; and the negative electrode sheet 10 of Example 2 maintains a capacity retention rate of more than 80% for a cycle number of more than 700 cycles, and the maximum cycle number can even reach more than 800 cycles, and the rate performance is extremely excellent. The negative electrode sheet 10 of Example 2 has fast conduction and reaction capabilities, as well as high capacity and stability, and the battery has excellent fast charging performance.
[0155] The above is a description of the negative electrode sheet 10 and the preparation method thereof, and the battery 100 provided in the embodiment of the present application.
[0156] The negative electrode sheet provided in the embodiment of the present application includes a current collector, a first negative electrode coating arranged on the surface of the current collector, and a second negative electrode coating arranged on the side of the first negative electrode coating away from the current collector, wherein the first negative electrode active material has a first rate, the second negative electrode active material has a second rate, and the first rate is less than the second rate; the current collector surface of the negative electrode sheet of the present application includes a double-layer coating, and a second negative electrode coating with a larger rate is provided as an outer layer to provide a fast ion transmission channel, so that the lithium ions outside the negative electrode sheet can quickly reach the inner layer through the outer layer for layer storage, and achieve rapid reception and conduction of current, thereby improving the fast charging performance of the battery; the first negative electrode coating with a smaller rate is provided as the inner layer, so that the inner layer has a large and stable capacity to absorb the lithium ions transmitted by the outer layer, thereby increasing the capacity of the battery; and the first negative electrode coating is stable in nature, which can alleviate the structural changes in the material of the second negative electrode coating, reduce the occurrence of side reactions, and thus ensure the overall stability and safety of the battery. The embodiment of the present application also provides a method for preparing a negative electrode sheet and a battery, which have the above-mentioned beneficial effects.
[0157] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A negative electrode sheet, characterized in that: include: current collector; A first negative electrode coating is disposed on the surface of the current collector, wherein the first negative electrode coating comprises a first negative electrode active material; A second negative electrode coating is disposed on a side of the first negative electrode coating away from the current collector, and the second negative electrode coating comprises a second negative electrode active material; The first negative electrode active material has a first magnification, the second negative electrode active material has a second magnification, and the first magnification is smaller than the second magnification.
2. The negative electrode sheet according to claim 1, characterized in that: At the same rate and at a capacity retention rate not lower than a set capacity retention rate, the number of cycles X that the first negative electrode active material can maintain is less than the number of cycles Y that the second negative electrode active material can maintain.
3. The negative electrode sheet according to claim 2, characterized in that: YX≥100.
4. The negative electrode sheet according to claim 3, characterized in that: The first negative electrode active material maintains a cycle number of between 300 and 400 at a capacity retention rate of not less than 80% at a first rate, the second negative electrode active material maintains a cycle number of between 500 and 600 at a capacity retention rate of not less than 80% at the first rate, and the second negative electrode active material maintains a cycle number of between 300 and 400 at a capacity retention rate of not less than 80% at a second rate.
5. The negative electrode sheet according to claim 4, characterized in that: The first magnification is 3C to 5C, and the second magnification is 6C to 10C.
6. The negative electrode sheet according to claim 1, characterized in that: The percentage of the mass of the first negative electrode coating to the sum of the masses of the first negative electrode coating and the second negative electrode coating is w1%, and the percentage of the mass of the second negative electrode coating to the sum of the masses of the first negative electrode coating and the second negative electrode coating is w2%, wherein w1%:w2%=(60%~80%):(20%~40%).
7. The negative electrode sheet according to claim 1, characterized in that: The first negative electrode active material includes primary graphite particles, and / or the second negative electrode active material includes secondary graphite particles.
8. The negative electrode sheet according to claim 1, characterized in that: The first negative electrode active material includes first graphite particles, and the particle size of the first graphite particles is 11.3 μm to 11.7 μm; And / or, the second negative electrode active material includes second graphite particles, and the particle size of the second graphite particles is 6.5 μm to 7.5 μm.
9. The negative electrode sheet according to claim 1, characterized in that: The orientation degree of the first negative electrode active material is 10.4 to 11.4; And / or, the orientation degree of the second negative electrode active material is 8.4 to 8.
7.
10. A method for preparing a negative electrode sheet, characterized in that: The following steps are involved: S10, providing a fluid collector; S20, selecting a material with a first magnification as a first negative electrode active material, and selecting a material with a second magnification as a second negative electrode active material, wherein the first magnification is smaller than the second magnification; S30, using the first negative electrode active material to prepare a first negative electrode coating material, and using the second negative electrode active material to prepare a second negative electrode coating material; S40, coating the first negative electrode coating material on the surface of the current collector to form a first negative electrode coating; S50, coating the second negative electrode coating material on a side of the first negative electrode coating facing away from the current collector to form a second negative electrode coating.
11. The method for preparing a negative electrode sheet according to claim 10, characterized in that: The step S20 comprises: S21, setting the same rate to measure the capacity retention rate and the number of cycles of the materials in turn, selecting a material that can maintain a capacity retention rate of not less than the set number of cycles X as the first negative electrode active material, and selecting a material that can maintain a capacity retention rate of not less than the set number of cycles Y as the second negative electrode active material, wherein X is less than Y.
12. The method for preparing a negative electrode sheet according to claim 11, characterized in that: The step S21 also includes YX≥100.
13. The method for preparing a negative electrode sheet according to claim 10, characterized in that: In step S20, Selecting the first negative electrode active material including first graphite particles, wherein the particle size of the first graphite particles is 11.3 μm to 11.7 μm; and / or, selecting the second negative electrode active material comprising second graphite particles, wherein the particle size of the second graphite particles is 6.5 μm to 7.5 μm; and / or, selecting the first negative electrode active material having an orientation degree between 10.4 and 11.4; And / or, the second negative electrode active material is selected with an orientation degree between 8.4 and 8.
7.
14. A battery, characterized in that: It comprises a negative electrode sheet as described in any one of claims 1 to 9, or a negative electrode sheet prepared by the preparation method as described in any one of claims 10 to 13, and also comprises a positive electrode sheet and a separator, wherein the negative electrode sheet, the separator and the positive electrode sheet are stacked, and the separator is arranged between the positive electrode sheet and the negative electrode sheet.
Citation Information
Patent Citations
Negative plate, preparation method of negative plate and battery
CN112599719A
Lithium ion battery negative plate, battery and preparation method of lithium ion battery negative plate
CN113270579A
High-rate lithium ion battery negative plate, preparation method thereof and lithium ion battery
CN113363418A
Negative plate and lithium ion battery
CN113675365A
Negative pole piece, preparation method thereof and secondary battery
CN114927639A